The very noisy night - Hendry, Diana, 1941-; Chapman, Jane, 1970- (New York : Dutton Children's Books, 1999)
Disturbed by the many peculiar sounds he hears while trying to get to sleep, Little Mouse repeatedly asks to get into bed with Big Mouse.
Keywords: Sound -- Fiction; Bedtime -- Fiction; Night -- Fiction; Fear -- Fiction; Mice -- Fiction